2007
DOI: 10.4049/jimmunol.179.7.4616
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Enhances Murine Dendritic Cell Migration to Draining Lymph Nodes via the Balance of Matrix Metalloproteinases and Their Inhibitors

Abstract: Cancers escape immune surveillance through the manipulation of the host’s immune system. Sequestration of dendritic cells (DCs) within tumor tissues and the subsequent inhibition of their migration is one of the several mechanisms by which tumors induce immunosuppression. In view of recent findings depicting the improvement of tumor immune responses in cancer patients following all-trans retinoic acid (ATRA) treatment, we sought to identify the effects of ATRA on DC mobility in the context of tumor immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 60 publications
5
59
0
2
Order By: Relevance
“…There was no significant difference in the efficacy of benazepril compared with ATRA in enhancing the expression of MMP-2/MMP-9. There are reports of a similar effects of ATRA: MMP-2 and MMP-9 were found to have increased in murine dendritic cells [25]. Marín et al [26] found that levels of both MMP-2 and MMP-9 were diminished in the renal basement membranes of newborn male rats fed a vitamin A-deficient diet [26].…”
Section: Discussionmentioning
confidence: 91%
“…There was no significant difference in the efficacy of benazepril compared with ATRA in enhancing the expression of MMP-2/MMP-9. There are reports of a similar effects of ATRA: MMP-2 and MMP-9 were found to have increased in murine dendritic cells [25]. Marín et al [26] found that levels of both MMP-2 and MMP-9 were diminished in the renal basement membranes of newborn male rats fed a vitamin A-deficient diet [26].…”
Section: Discussionmentioning
confidence: 91%
“…As such, the increased induction of TIMP-1 in response to PGE 2 probably inhibited the migration-promoting effects of MMP-9, a hypothesis supported by a previous report demonstrating that the balance of MMP-9 and TIMP expression is of crucial for DC migration in vivo. 58 Taken together, we have shown that LTC 4 may represent a promising candidate to replace PGE 2 in DC maturation protocols that may lead to enhanced immunogenicity of DC-based cancer vaccines. The results presented in this study warrant further investigation of this novel maturation protocol in animal tumor models, and ultimately, in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, proteinases and factors that regulate their activity are now recognized to serve as key regulators of cell migration and spreading in cancer biology and development, model systems that may be instructive in studying kidney injury. [18][19][20] In this study, we investigated the role of kidney pericytes in vascular stabilization and the central role that pericytes play in regulating protease activity of the vasculature.…”
mentioning
confidence: 99%